2021
DOI: 10.1111/ajt.16233
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin as a preventive strategy against BK virus viremia and BKV-associated nephropathy in kidney transplant recipients—Results from a proof-of-concept study

Abstract: BK virus (BKV) replication occurs frequently in kidney transplant recipients (KTR), potentially leading to BKV-associated nephropathy (BKVAN) and graft loss. Patients with high titers of BKV-neutralizing antibodies (NAbs) are protected against BKV replication, and intravenous immunoglobulin (IVIg) infusion can increase NAb titers. We investigated whether early IVIg administration prevents BKV replication in patients with low NAb titers (<4 log 10 against the BKV-specific genotype). Based on NAb titers on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…These findings may explain the lack of improved kidney allograft outcomes in the IVIG‐treated KTRs. Our findings are not contradictory to very recent findings on the successful use of IVIG for BKV‐prophylaxis [20], since BKV‐specific neutralizing antibodies and B‐cell immunity have been associated with prevention of BKV‐replication, but BKV‐specific T‐cell immunity has been associated with the control of BKV‐replication [6,7,21]. There are two recent studies investigating IVIG treatment for BKV‐DNAemia.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These findings may explain the lack of improved kidney allograft outcomes in the IVIG‐treated KTRs. Our findings are not contradictory to very recent findings on the successful use of IVIG for BKV‐prophylaxis [20], since BKV‐specific neutralizing antibodies and B‐cell immunity have been associated with prevention of BKV‐replication, but BKV‐specific T‐cell immunity has been associated with the control of BKV‐replication [6,7,21]. There are two recent studies investigating IVIG treatment for BKV‐DNAemia.…”
Section: Discussionsupporting
confidence: 71%
“…Very recently, intravenous Immunoglobulins (IVIG), that have been shown to contain high amounts of neutralizing BKV‐specific antibodies in vitro [19], have been suggested for BKV prophylaxis in KTRs with low neutralizing BKV‐specific antibody titres [20]. However, using intravenous Immunoglobulins (IVIG) to treat active BKV‐replication remains controversial and showed limited impact on BKV‐clearance [21‐23].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent publication retrospectively evaluated patients who received IVIG prophylaxis (for either secondary immune deficiency or the prevention or treatment of AMR) during the first 3 months posttransplant and compared them on the basis of BK risk stratification to those who did not receive IVIG in the first 3 months posttransplant. At 12 months posttransplant, the authors found the incidence of BK viremia in patients in the high‐risk group (having low BK neutralizing antibodies) that received IVIG (6.9%, 3 of 44 patients) was similar to the incidence of the low‐risk group that did not receive IVIG (10.1%, 9 of 88 patients) but significantly lower than the high‐risk group that did not receive IVIG (36.6%, 15 of 41 patients; p < 0.001) 197 . Robust studies evaluating BKV treatment and prophylaxis strategies are needed in both adult and pediatric KTRs.…”
Section: Infection Prophylaxis In Pediatric Renal Transplantationmentioning
confidence: 64%
“…Several previous studies have shown that the antiviral CTL response plays a key role in BKPyV clearance (Binggeli et al, 2007; Leboeuf et al, 2017; Schachtner et al, 2011), leading to the development of cellular immunotherapy for active BKPyV replication in the context of HSCT (Papadopoulou et al, 2014; Tzannou et al, 2017) and solid organ transplant (Nelson et al, 2020). With respect to the BKPyV-specific humoral response, it has been observed that the incidence of PyVAN is higher in KTx recipients with low ELISA (Bohl et al, 2008) and neutralizing antibody titres (Solis et al, 2018), and some studies and case reports have indicated that infusion of intravenous immunoglobulin (IVIG) containing BKPyV-specific neutralizing antibodies (Velay et al, 2019), can prevent active BKPyV replication in KTx recipients (Benotmane et al, 2021), and successfully treat PyVAN (Hwang et al, 2018; Matsumura et al, 2020; Piburn & Al-Akash, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the BKPyV-specific humoral response, it has been observed that the incidence of PyVAN is higher in KTx recipients with low ELISA (Bohl et al, 2008) and neutralizing antibody titres (Solis et al, 2018) , and some studies and case reports have indicated that infusion of intravenous immunoglobulin (IVIG) containing BKPyV-specific neutralizing antibodies (Velay et al, 2019) , can prevent active BKPyV replication in KTx recipients (Benotmane et al, 2021) , and successfully treat PyVAN (Hwang et al, 2018;Matsumura et al, 2020;Piburn & Al-Akash, 2020) .…”
Section: Introductionmentioning
confidence: 99%